2021
DOI: 10.1021/acsaem.1c00259
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Two-Electron Oxygen Reduction Reaction Performance of Carbon Nanospheres by Pore Engineering

Abstract: Electrochemical production of hydrogen peroxide from the two-electron oxygen reduction reaction (ORR) is emerging as a promising method for in situ production of H 2 O 2 . However, carbon materials, one of the most prospective catalysts for the twoelectron ORR, remain not active enough for mass production of H 2 O 2 in acidic or neutral media. Pore channel engineering is an effective strategy to enhance the ORR activity of carbon materials by enlarging the electrochemically accessible surface and facilitating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…9 a) [ 146 ]. Recently, Huang et al prepared carbon nanospheres with different pore sizes using phenolic resin spheres as the precursor for studying their ORR performances [ 144 ]. The results showed that catalysts with rich mesopores enabled more accessible contact areas for O 2 and electrolyte ions, thus presenting better 2e – -ORR performance (Fig.…”
Section: Designs Of Electrocatalysts For 2e – -Orrmentioning
confidence: 99%
See 1 more Smart Citation
“…9 a) [ 146 ]. Recently, Huang et al prepared carbon nanospheres with different pore sizes using phenolic resin spheres as the precursor for studying their ORR performances [ 144 ]. The results showed that catalysts with rich mesopores enabled more accessible contact areas for O 2 and electrolyte ions, thus presenting better 2e – -ORR performance (Fig.…”
Section: Designs Of Electrocatalysts For 2e – -Orrmentioning
confidence: 99%
“…b Schematic illustration of mesopores for facilitating O 2 transport. Reproduced with permission [ 144 ]. Copyright 2021, American Chemical Society.…”
Section: Designs Of Electrocatalysts For 2e – -Orrmentioning
confidence: 99%
“…In 1939, Berl 88 first reported the preparation of H 2 O 2 by 2e − ORR on carbon electrodes. Subsequent researchers found that carbon allotropes have different catalytic performances for 2e − ORR, such as graphite, 89 graphene, 33,90 porous carbon, 91 carbon nanospheres, 32 and other applications in electrode catalytic materials were studied. However, the catalytic activity of pure carbon materials is generally not ideal.…”
Section: Carbon-based Catalystsmentioning
confidence: 99%
“…It also has high selectivity and stability for the generation of hydrogen peroxide. Because the pore size significantly affects hydrogen peroxide generation, Huang et al 91 prepared carbon nanospheres with different pore sizes by a soft templating method (Figure 12C,D). The pore size-optimized catalyst exhibits excellent 2e − ORR activity in alkaline and neutral media.…”
Section: Aperturementioning
confidence: 99%
“…Previously, there have been numerous reports on developing strategies to tune the pore structure of the Fe/N/C electrocatalysts with improved ORR activity. Among them, the template-sacrificing method is one of the most popular strategies. Taking Si or SiO 2 templates as an example, they were first mixed with a carbon precursor, followed by a pyrolysis step, and finally removed by a posttreatment process to build up the pores. , Although the template method can introduce tailorable mesopores, the posttreatment media involved corrosive HF or concentrated KOH and significantly changed the surface structure and composition of the electrocatalysts. ,, These changes may partially offset the efforts to enhance the ORR activity induced by variation of the pore structure.…”
Section: Introductionmentioning
confidence: 99%